2022
DOI: 10.1002/esp.5525
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting views of gully erosion in South Africa

Abstract: Gully erosion is an environmental problem recognized as one of the worst land degradation processes worldwide. Insight into regional gully perturbations is required to combat the serious on‐ and off‐site impacts of gullying on a catchment management scale. In response, we intersect different perspectives on gully erosion‐specific views in South Africa (SA), a country that exhibits various physiographic properties and spans 1.22 million km2. While the debate surrounding gully origin continues, there is consensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 124 publications
0
15
0
Order By: Relevance
“…A recent review by Olivier et al (2023) showed contemporary gullying to be a continued concern in SA. Gully erosion rates of up to 25.7 t ha −1 year −1 (Grellier et al, 2012) are documented, which increases to up to 123.7 t ha −1 year −1 (Favis‐Mortlock et al, 2018) when badlands are included.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent review by Olivier et al (2023) showed contemporary gullying to be a continued concern in SA. Gully erosion rates of up to 25.7 t ha −1 year −1 (Grellier et al, 2012) are documented, which increases to up to 123.7 t ha −1 year −1 (Favis‐Mortlock et al, 2018) when badlands are included.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the database and a recent literature review of gully erosion in SA (Olivier et al, 2023), five broad categories were identified to include in the susceptibility model, namely, topography, soil, geology, climate and anthropogenic activities. Seven control factor datasets were selected to represent these five broad categories, all of which were limited to national extents (where spatial resolution is not indicated, the dataset consisted of vector data) (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations